Hybrid and vaccine‐induced immunity against SAR‐CoV‐2 in MS patients on different disease‐modifying therapies. Issue 10 (27th September 2022) - Kister, Ilya; Curtin, Ryan; Pei, Jinglan; Perdomo, Katherine; Bacon, Tamar E.; Voloshyna, Iryna; Kim, Joseph; Tardio, Ethan; Velmurugu, Yogambigai; Nyovanie, Samantha; Valeria Calderon, Andrea; Dibba, Fatoumatta; et al.
Abstract: Objective: To compare "hybrid immunity" (prior COVID‐19 infection plus vaccination) and post‐vaccination immunity to SARS CoV‐2 in MS patients on different disease‐modifying therapies (DMTs) and to assess the impact of vaccine product and race/ethnicity on post‐vaccination immune responses. Methods: Consecutive MS patients from NYU MS Care Center (New York, NY), aged 18–60, who completed primary COVID‐19 vaccination series ≥6 weeks previously were evaluated for SARS CoV‐2‐specific antibody responses with electro‐chemiluminescence and multiepitope bead‐based immunoassays and, in a subset, live virus immunofluorescence‐based microneutralization assay. SARS CoV‐2‐specific cellular responses were assessed with cellular stimulation TruCulture IFNγ and IL‐2 assay and, in a subset, with IFNγ and IL‐2 ELISpot assays. Multivariate analyses examined associations between immunologic responses and prior COVID‐19 infection while controlling for age, sex, DMT at vaccination, time‐to‐vaccine, and vaccine product. Results: Between 6/01/2021 and 11/11/2021, 370 MS patients were recruited (mean age 40.6 years; 76% female; 53% non‐White; 22% with prior infection; common DMT classes: ocrelizumab 40%; natalizumab 15%, sphingosine‐1‐phosphate receptor modulators 13%; and no DMT 8%). Vaccine‐to‐collection time was 18.7 (±7.7) weeks and 95% of patients received mRNA vaccines. In multivariate analyses, patients with laboratory‐confirmed prior COVID‐19 infection had significantly increased antibody and cellular post‐vaccination responses compared to those without prior infection. Vaccine product and DMT class were independent predictors of antibody and cellular responses, while race/ethnicity was not. Interpretation: Prior COVID‐19 infection is associated with enhanced antibody and cellular post‐vaccine responses independent of DMT class and vaccine type. There were no differences in immune responses across race/ethnic groups.